Physical activity, exercise, and mental health of healthy adolescents: A review of the last 5 ​years - Eva Ruiz-Ranz; Iván Asín-Izquierdo (Sports Medicine and Health Science)
The mental health of adolescents is a priority for successful development. Physical activity (PA) and exercise can have effects on the mental health of adolescents. This review analysed the effect that physical exercise interventions can have on the mental health of healthy adolescents between 10 and 19 years of age. The search was carried out in four databases. PubMed, Web of Science, Scopus and SportDiscuss, were searched up to December 31, 2022, following the general model. Eleven studies were selected, with a total sample of 23 ​681 participants in 2 435 studies published in the last 5 years involving healthy adolescents. The search process and review of the articles was performed by independent expert investigators. The risk-of-bias and the methodological quality were analysed using the Cochrane scale. The limited and heterogeneous studies conducted so far do not clearly establish the benefits of PA on adolescents’ mental health. However, some PA interventions seem to improve subjective well-being, self-esteem, physical and mental well-being, anxiety, lifestyle, emotional intelligence, depressive mood, and perceived benefit and confidence in healthy adolescents. It is important to design an effective and appropriate physical exercise programme that can be implemented for adolescents to achieve significant effects on their mental health. Studies that did not implement an appropriate exercise program with improvements in adolescent physical fitness showed no changes in psychological variables. Further research is needed to clearly establish that exercise programmes have positive effects on mental health in healthy adolescents.